LEAN MANUFACTURING IMPLEMENTATION: AN APPROACH TO REDUCE PRODUCTION COST - Iraswari Iraswari; Helmy Adam (Universitas Brawijaya, 2012)
Abstract: Lean Manufacturing Implementation: An Approach To Reduce Production Cost. Opportunities to improve production processes and reduce production cost through the implementation of lean manufacturing in small medium garment manufacturing are presented in this research. This research shows that there is a possibility of decrease in production cost and increase in return on sales. Lean manufacturing implementation can eliminate waste in the production process. This is a set of techniques for identification and elimination of waste gathered from The Ford Production, Statistical Process Control and other techniques. Improvement of quality could be carried out while time and cost of production are being reduced. Abstrak: Implementasi Lean Manufacturing: Suatu Pendekatan Biaya Produksi. Kesempatan untuk memperbaiki proses produksi melalui implementasi lean manufacturing di sebuah usaha produksi garmen kecil dan menengah, dipresentasikan dalam artikel ini. Riset ini menunjukkan bahwa ada kemungkinan untuk mengurangi biaya produksi dan meningkatkan tingkat pengembalian penjualan. Implementasi lean manufacturing dapat mengeliminasi pembuangan dalam proses produksi. Ini merupakan suatu set teknik pengeindentifikasian and pengeliminasian pembuangan yang diambil dari The Ford Production, Statistical Process Control dan teknik lain. Perbaikan kualitas dapat diperbaiki pada saat yang sama waktu dan biaya dapat direduksi.